Independence of students in learning science: A study in San Isidro National High School, Lupao City - Josel De Guzman (Indonesian Journal of Education Research (IJoER), 2020)
Purpose of the study: This research aims to explore the independence of students in learning science. Methodology: This research is a mixed research, which combines quantitative and qualitative approaches. The quantitative approach is shown by descriptive statistical data, while the qualitative approach is shown by the results of the interview. The sample of this study was 9th grade students at San Isidro National High School. Main Findings: The results in this study indicate that the majority of students have a fairly good independence character in learning science, as indicated by the results of descriptive statistics, which shows as many as 34.9% of students have moderate independence. The remaining 6.6% of students are categorized as very low, 23.6% of students are categorized as low, 25.5% are categorized as high, and 9.4 students are categorized as very high. Applications of this study: This research is very useful for science teachers in identifying and knowing the picture of students' independent character in learning science, especially in the Philippines. Novelty/Originality of this study: This research only focuses on looking at the students' independent character in learning Natural Sciences, at San Isidro National High School, especially grade 9.